Financial practices and problems amongst elderly in Malaysia - Masud, Jariah; Sulaiman, Husna; Tengku Abdul Hamid, Tengku Aizan; Ibrahim, Rahimah (Universiti Putra Malaysia Press, 2012)
Being old is often associated with poverty, as a result of limited access to financial resources due to retirement or deterioration in health. The high incidence of poverty among the elderly is a global concern. How much the elderly have is important but how they use what they have is equally important. This paper focuses on financial practice and problems of the elderly in Malaysia. Data used in the analysis were collected in 2004 from among 2,327 elderly aged between 55 and 75 years. Samples were selected using multi stage systematic sampling. Financial practice was measured using 12 statements representing four dimensions, namely, planning, cash management, credit and investment. Financial problems were measured using seven items with two dimensions, namely, daily problems and credit management. In general, the elderly in the study performed basic financial practice (planning and cash management) but a lower percentage of these elderly performed credit and investment plans. About one third of elderly had experienced at least one of the seven financial problems listed. Multiple regression analysis conducted to explore the factors explaining variation in financial practice revealed that the model explained 20.7% variation in the financial practice score. The variable significantly explained the variations in the financial practice score were gender, age, region, ethnicity, education, home ownership, health perception, and income. A further research is needed to better understand the dynamic of financial practice among the elderly.